2015
DOI: 10.1007/s00467-015-3201-8
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in children following renal transplantation—results from the ESPN/ERA-EDTA Registry

Abstract: Anemia is present in a significant proportion of European pediatric kidney transplant recipients and is associated with renal allograft dysfunction and type of immunosuppressants used. In our patient cohort, higher Hb levels were associated with better graft and patient survival and less hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 40 publications
6
25
0
1
Order By: Relevance
“…32 In a recent report on PTA in children from the ESPN/ERA-EDTA registry, patients on tacrolimus had slightly higher Hb levels than those on cyclosporin. 33 A vast majority of our patients were treated with tacrolimus; hence, we were unable to compare the prevalence of anemia between the two groups. In our study, no difference was found between the two groups.…”
Section: Epo Levels (In Patients Who Did Not Receive Epo Supplementatmentioning
confidence: 98%
“…32 In a recent report on PTA in children from the ESPN/ERA-EDTA registry, patients on tacrolimus had slightly higher Hb levels than those on cyclosporin. 33 A vast majority of our patients were treated with tacrolimus; hence, we were unable to compare the prevalence of anemia between the two groups. In our study, no difference was found between the two groups.…”
Section: Epo Levels (In Patients Who Did Not Receive Epo Supplementatmentioning
confidence: 98%
“…Tacrolimus was introduced in the 1990s as an alternative to ciclosporin and is now widely used to prevent rejection after solid-organ transplantation in both adult and pediatric transplant recipients [1]. At the time of discharge after transplantation, approximately 70% of pediatric kidney transplant patients are treated with tacrolimus [2]. Tacrolimus is characterized by a narrow therapeutic index: high concentrations are associated with toxicity, malignancy, and infection, while low concentrations are associated with an increased risk of acute rejection [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…According to recent registry data, 60–70% of paediatric renal transplant recipients are treated with tacrolimus at the time of discharge after transplantation . Consequently, the vast majority of these children are exposed to this drug during the remainder of their childhood years towards adulthood.…”
Section: Introductionmentioning
confidence: 99%